Transportasi Yang Terintegrasi di Wisata Cagar Budaya Kota Tua Jakarta - Elfrida Ratnawati; Siti Nurbaiti (Universitas Semarang, 2023)
The purpose of writing this article is to discuss integrated transportation in old city Jakarta. Thereare many problems faced and must be solved in order to achieve the realization of integrated transportation, so as to create a neatly organized city and to travel to the old city area, tourists must feel comfort and time efficiency. The problem faced today is that transportation to the cultural heritage of the old city is very difficult because so much land transportation passes through the old city but is not properly arranged by the city government, so there is always congestion. This writing is a normati f legal research that uses secondary data and then analyzed descriptively. This research is important to answer the problem of using fast, convenient and efficient land transportation to achieve the cultural heritage tourism of the old city in the Jakarta area. The results of this study explain that the planning of the old city area of Jakarta so that its potential is maximized through the arrangement of integrity and sustainable transportation issued by the DKI Jakarta City Government so that the arrangement of the old city is expected to become a valuable property center and grow the economy with the advantages of the old city as a business city and tourist city. Tujuan penulisan artikel ini adalah membahas transportasi yang terintegrasi di Kota Tua Jakarta. Banyak permasalahan yang dihadapi dan harus diselesaikan agar dapat mencapai terwujudnya transpotasi yang terintegrasi, sehingga tercipta kota yang tertata dengan rapi dan untuk berwisata menuju wilayah kota tua para turis harus merasakan kenyamanan dan efesiensi waktu. Permasalahan yang dihadapi saat ini adalah transportasi menuju cagar budaya kota tua sangat sulit disebabkan begitu banyak transportasi darat yang melewati kota tua tetapi tidak ditata dengan baik oleh pemerintah kotanya, sehingga selalu terjadi kemacetan. Penulisan ini merupakan penelitian hukum normatif yang menggunakan data sekunder kemudian dianalisis secara dekriptif. Penelitian ini penting dilakukan untuk menjawab permasalahan penggunaan transportasi darat yang cepat, nyaman dan efisien untuk mencapai wisata cagar budaya kota tua di wilayah Jakarta. Hasil penelitian ini menjelaskan bahwa perlu penataan kawasan kota tua Jakarta agar potensinya menjadi maksimal melalui penataan transportasi yang terintegritas dan berkelanjutan yang dikeluarkan oleh Pemerintah Provinsi DKI Jakarta agar penataan kota tua diharapkan menjadi pusat properti yang bernilai dan menumbuhkan ekonomi dengan keunggulan kota tua sebagai kota bisnis dan kota wisata.